Teaching History With Digital Historical Games: An Introduction to the Field and Best Practices. (August 2016) - McCall, Jeremiah
Background: Writing about the theory and best practices of using history-themed video games in the classroom stretches back at least to the 1980s. However, the literature on the subject is scattered, making it difficult for history educators considering the use of historical games. Purpose: This article provides an introduction for history educators to the use of computer-based historical games in history education. In this article, I provide differing definitions for types of historical games and discuss the importance of such distinctions for the history educator. I provide the strengths and biases inherent in the medium of computer-based historical games. Results: This article surveys best practices from the literature concerning the use of historical games in history class. The article concludes with a brief survey of potentially useful historical games.